GAMBARAN PERILAKU KONSUMSI SUSU PADA SISWA SMP AR-RAHMAN MEDAN TAHUN 2012 - Maya Sari Hasibuan; Evawany Y Aritonang; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Milk hasthe most complete nutrient source and it is good for all ages including schoolchildren. School children age is in development and growth phase, hence it is necessaryto increasemilk drinking behaviour.The objective of this researchwas to know the behaviour of milk consumption of the students ofJunior High School Ar-rahman Medan in 2012.The method usedwas survey with descriptive and cross sectional approach. The samples of research were 70 students of the total 230 students. Sampletaking technique was done with proportional sampling that was by seeing the amount of the students from each class namely class VII for 21 students, class VIII for 22 students, and class IX for 27 students.The results of research showed that 85.7% of the knowledge of students were categorized good, 51.4% of the attitude of the students were categorized good, and 78.6% of the actions of the students were categorized less good.Good knowledge and attitude do not guarantee good action forever. Conversely, it may even that the action of the student was less good. It is suggested for the management of Junior High School Ar-Rahman Medanto give information and counseling regarding the consumption of milk in detail, better understanding about the type of milk and this contents. Keyword: Behaviour, StudentsandMilkConsumptio